Finite element analysis of local shear buckling in corrugated web beams. (1st May 2018) - Aggarwal, Karnik; Wu, Sam; Papangelis, John
Highlights: Local shear buckling of beams with trapezoidal corrugated webs analysed using FEA. Elastic buckling analyses on 90 cantilever beams were performed. Influence of web thickness, panel width and web height was investigated. Shear buckling coefficient was compared against existing theoretical equations. Equation to approximate the local shear buckling coefficient is recommended. Abstract: A corrugated web beam (CWB) is a variation to the universal hot rolled or welded I section. CWBs usually comprise of wide thick plate flanges and a thin corrugated web. Due to the accordion effect shear is carried primarily by the corrugated web while bending moments are resisted by the flanges. Under shear action three different modes of shear buckling may be realised in the web – local, global or interactive. This paper describes analyses performed to investigate the local shear buckling behaviour of beams with trapezoidal corrugated webs. Finite element models of cantilever beams with different web geometries were prepared and an elastic eigenvalue buckling analysis was performed using the program ABAQUS. The influence of web thickness, panel width and web height on the local shear buckling coefficient kL was investigated. Values of kL were compared against existing equations from theory and other research. The effect of these dimensions on the local shear buckling stress was also considered. In total, 90 models were analysed. Overall, it was found that the value of kL lies between 5.34 and 8.98. This corresponds to panel boundary conditions that are between simply supported and clamped. The analysis results revealed that kL increases with stockier panels (large panel width to height ratio) but decreases with thicker webs. When the panel width was decreased, local shear buckling occurred at larger stress values. Similar results were observed when the web height was decreased and the panel thickness was increased. These results are consistent with plate buckling theory. Finally, based on these findings an equation to approximate the local shear buckling coefficient in corrugated web beams is recommended.